The influence of security perceptions on intention to shop online :|ba case study of Klang Valley region - Ali, Najma Imtiaz (Kulliyyah of Information and Communications Technology, International Islamic University Malaysia, 2019)
Online shopping use in Malaysia has grown and has transcended the lives of many, as it offers unprecedented conveniences. However, security and privacy are two most important concerns related to online shopping are widely prevalent and are considered as barriers to realizing the online shopping’s fullest potential in Malaysia. It is also found from previous studies and literature that customers are always worried about the financial and system security. In addition to security and privacy another factor of deep concern is cybercrime. Generally, many studies have been done to understand customers’ behaviour during online shopping. To be best of the knowledge there is need to investigate further on customer intention to shop online through factors such as trust, financial security, system security, privacy and cybercrime. This research proposes a model considering intention to shop online as dependent variable, and financial security, privacy, system security and cybercrime as independent variables and trust factor as a mediator between the independent and dependent variable. This study adopted a quantitative survey questionnaire method for data collection using simple random sampling. The questionnaire was distributed among Internet users. In total 400 valid responses were found complete and are used for data analysis. Statistical Package for Social Sciences (SPSS) and Analysis of a Moment Structures (AMOS) with Structural Equation Modelling (SEM) approach were used to analyse and validate the proposed model. Research findings show that 05 out of 06 hypotheses were found to be statistically significant, leaving 1 as insignificant. The results obtained through statistical analysis quantified a strong relationship among security factors with a variance of 71.3% in trust, and 67.6% in intention to shop online. In addition, the findings revealed that financial security and privacy are important to acquire customer trust as well intention, whereas system security have a negative influence towards the trust during the online shopping. Furthermore, the cybercrime has a negative influence on the trust and intention to shop online. The findings of this study are valued to stakeholders interested in e-retailing. Potential stakeholders would benefit from an improved and revised understanding of these aspects in order to develop business strategy and service competence in online shopping.